IDENTITAS POSTKOLONIAL PEREMPUAN SIRO-FENISIA DALAM MARKUS 7:24-30 - Imanuel Teguh Harisantoso (Regula Fidei: Jurnal Pendidikan Agama Kristen, 2019)
Text "The Syro-phoenician woman who believes" in Mark 7:24-30 in a postcolonial study approach is a passion to combating colonialism, neo-colonialism, dictatorism, social separation of societies, religion and racial (SARA) and social injustice. This matter done to realize readers of the Bible as they are in a situation of being colonized, because attempting to negotiate toward liberation and equality. In the postcolonial context, Jesus encounter with the Greek women of the Syro-Phoenician was a symbolic and imaginative meeting of two peoples (nations), Jews and Greeks, cultural dialectics, traditions and believed. For the Jews who were narrated as having a dominant culture, labeled the Syro-phoenician woman as inferior and weak, proper to be helped and pitied, therefore worthy of being called a dog. As a "dog" this woman received a new identity from the superior. The resistance and rejection of the Syro-phoenician woman on the new identity of the postcolonial received issued intense communication and relationships. At first it was seen as liyan and the other, but now the stereotype is melting and developing into sisters and brothers. The dialectic between them are brings peacefulness: alignment and equality.